2016
DOI: 10.1371/journal.pone.0162228
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule-Induced Complement Factor D (Adipsin) Promotes Lipid Accumulation and Adipocyte Differentiation

Abstract: Adipocytes are differentiated by various transcriptional cascades integrated on the master regulator, Pparγ. To discover new genes involved in adipocyte differentiation, preadipocytes were treated with three newly identified pro-adipogenic small molecules and GW7845 (a Pparγ agonist) for 24 hours and transcriptional profiling was analyzed. Four genes, Peroxisome proliferator-activated receptor γ (Pparγ), human complement factor D homolog (Cfd), Chemokine (C-C motif) ligand 9 (Ccl9), and GIPC PDZ Domain Contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 38 publications
(57 reference statements)
4
73
0
5
Order By: Relevance
“…Acylation-stimulating protein (ASP/C3adesArg), a downstream degradation product of C3, can stimulate triglyceride synthesis and glucose transport in adipocytes through the actions of the C3a receptor C5L2 (20,32). Indeed, FD is sufficient to induce the expression of PPAR␥, a transcription factor involved in assimilation of lipid, in preadipocytes (50). Modulation of the adipose-liver axis is one potential mechanism by which FD could protect from ethanol-induced steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Acylation-stimulating protein (ASP/C3adesArg), a downstream degradation product of C3, can stimulate triglyceride synthesis and glucose transport in adipocytes through the actions of the C3a receptor C5L2 (20,32). Indeed, FD is sufficient to induce the expression of PPAR␥, a transcription factor involved in assimilation of lipid, in preadipocytes (50). Modulation of the adipose-liver axis is one potential mechanism by which FD could protect from ethanol-induced steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…FD, which is also called adipsin, is a 25-kDa protein that is predominantly synthesized in differentiated adipocytes (11)(12)(13) and is required for AP activity (14,15). In addition, FD also serves important roles outside of complement, because it is involved in adipogenesis (16), insulin secretion (17), and obesity (13). FD is genetically encoded with a short hexameric propeptide (11), and the original report of FD purification also identified a minor zymogenic FD fraction that could be activated by trypsin (18).…”
mentioning
confidence: 99%
“…Adipsin is an adipokine secreted by adipocytes that promotes adipocyte differentiation. 59 While a potential role for adipsin as a catabolic mediator in joint tissues requires further investigation, it has been reported that levels of adipsin are higher in the serum 60 and cartilage 61 of OA patients compared to non-OA controls. Adiponectin is mainly produced in adipocytes and plays an important role in thermoregulation.…”
Section: Discussionmentioning
confidence: 99%